Illustrated Anatomical Segmentectomy for Lung Cancer - Nomori, Hiroaki; Okada, Morihito; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2012)
Advances in computed tomography have made it possible to detect small lung cancers, which has changed lung cancer surgery from lobectomy to a lesser lobar resection such as a segmentectomy or wedge resection. Although wedge resection is a simple procedure, it has a higher risk of hilar lymph node or surgical margin recurrence than does a lobectomy. On the other hand, segmentectomy is a well-known curative surgery for small lung cancers. It is difficult to perform accurately, however, because of its anatomical complexity, which makes surgeons hesitant to use it. Illustrated Anatomical Segmentectomy for Lung Cancer provides readers a detailed explanation of segmentectomy with numerous easy-to-understand color illustrations showing the precise segmental anatomies for each pattern of the procedure. To better illustrate an accurate anatomical segmentectomy, the text shows details of anatomy during the procedure. Up to 25 patterns can be involved, each of which is shown in approximately 10 illustrations.
Part I General Statement -- Chapter 1 Nomenclature of Segments -- Chapter 2 General Knock of Segmentectomy -- Part II Details of Technique -- Chapter 3 Segmentectomy of the Right Upper Lobe -- Chapter 4 Segmentectomy of the Right Lower Lobe -- Chapter 5 Segmentectomy of the Left Upper Lobe -- Chapter 6 Segmentectomy of the Left Lower Lobe -- Chapter 7 Sleeve Segmentectomy -- Bibliography.
Keywords: Medicine; Oncology; Cancer -- Surgery; Surgery; Thoracic surgery; Medicine & Public Health; Medicine/Public Health, general; Surgery; Oncology; Thoracic Surgery; Surgical Oncology; General Surgery